E-015 Differential expression of cytokines in Mesenchymal stem cells as a potential target for Endovascular stem cell therapy. (14th July 2013) - Mir, O; Parsha, K; Nguyen, C; Yang, B; Savitz, S
Abstract : Background: Large vessel ischaemic stroke frequently leads to large ischaemic core and poor recovery in majority of patients. Extensive animal data indicate that allogeneic bone marrow derived mesenchymal stem cells (MSCs) improve outcome in rodent stroke models. Intra-arterial injection of MSCs is a potential therapeutic intervention for stroke treatment. The broad repertoire of secreted trophic and immunomodulatory cytokines produced by MSCs, has considerable potential for the treatment of cerebrovascular disease. In preparation for intra-arterial (IA) delivery we designed a series of experiments on MSCs intending to make a novel cell subtype with differential expression of cytokines leading to different functionality of the stem cell such as anti-inflammatory or vasculogenesis, in the setting of endovascular injection of MSCs after acute stroke by exposing them to different types of vehicles or microenvironment, which might lead to recovery. Methods: Human MSCs at P3 were derived from the bone marrow of a healthy volunteer expanded with human platelet lystate (HPL) at a GMP facility. The solutions tested were 5% Albumin (ALB), Hexstarch (Hx), Dextran, 5% Dextrose in NS (D5NS), and Growth Media (DMEM+ HPL), a control medium. All were used with or without 2.5 U/mL of heparin as Low dose heparin along with 10% iodine contrast dye (Omnipaque). We determined MSC viability in these solutions at room temperature for 5, 15, 30 and 60 mins. We then passed MSCs through a PROWLER SELECT LP catheter and assessed viability by flow cytometery using Propidium Iodide. Cytokine expression was checked at 5 and 60 mins including VEGF, IL-6, IL-8 and TNF-alpha. Results: Cell viability remained above 90% except in D5NS and was not altered after catheter passage nor after exposure to heparin with iodine contrast. Cells in albumin had the highest viability of more than 98%. There was no significant difference in viability among the different solutions. However expression of cytokines differed in different solutions as shown in fig1. Albumin only exposure led to increased VEGF expression more than any other solution. Also IL 6, IL 8 and TNF alpha expression can be suppressed by exposure to Dextran and Hexstarch. Conclusions: MSCs do not appear to be damaged by catheter passage or exposure to heparin, contrast and different solutions but the cytokine expression differs significantly. This study lends credence to customisation of MSCs by doing molecular preconditioning for individualisation of therapy. Disclosures: O. Mir: 1; C; NIH. K. Parsha: None. C. Nguyen: 1; C; NIH. B. Yang: None. S. Savitz: 1; C; NIH, Genentech. 2; C; Aldagen.